Analisis Tata Kelola Keamanan Data dan Kontinuitas Layanan Berdasarkan Framework COBIT 2019 pada Platform E-Commerce Lokal (Studi Kasus: MedanMart) - Oktaviana Bangun; Elysabeth Cry Aruan; Suci Aisa Sirait; Tiara Yedidha Keliat; Selvia englika br Sitepu; Peranika Br perangin angin (Universitas Mandiri Bina Prestasi, 2026)
Local e-commerce platforms and digital MSMEs in Indonesia currently encounter formidable obstacles regarding data security governance and maintaining service continuity. To address these issues, this research evaluates the management of data security and service stability at MedanMart, a prominent local e-commerce platform in Medan City, by utilizing the COBIT 2019 framework. The study specifically deep-dives into the DSS05 (Management of Security Services) and EDM03 (Ensuring Risk Optimization) domains to determine governance maturity, perform gap analysis, and formulate strategic improvements for digital business readiness. Employing an empirical, descriptive, and qualitative case study approach, data were gathered through field observations, policy document reviews, and semi-structured interviews with IT personnel, operations managers, and merchant representatives. The assessment results revealed a maturity score of 2.43 for DSS05 and 2.21 for EDM03, categorizing both at the